Implementasi Reward dan Punishment oleh Guru Pendidikan Agama Katolik Dalam Meningkatkan Minat Belajar Peserta Didik Sekolah Santo Petrus Medan - Sinulingga, Aldi; Br Milala, Grace Novianti (IN VERITATE LUX, 2023)
This study aims to determine the implementation of reward and punishment as well as students' interest in Catholic religious education lessons at school. Interest in learning is a feeling of liking and having an interest in something or an activity without being told so. Interest is basically accepting or establishing a relationship between oneself and something outside of oneself. Interest in learning can be measured using indicators of attention, relevance, confidence, and satisfaction. Giving rewards and punishments is used by Catholic Religious Education teachers as reinforcement and stimulus in education. The background of this research is the lack of interest in studying Catholic religious education. This is because religious education tends to be boring and taught using less creative methods. Based on this, researchers conducted research on the implementation of reward and punishment by Catholic Religious Education teachers in increasing students' interest in learning at St. Petrus Elementary School, Medan. This study uses a qualitative method. Data collection techniques included interviewing, observing, and interviewing. The informants in this study were Catholic Religious Education teachers, school principals, and students. The findings of this study indicate that the application of reward and punishment can increase students' interest in learning. Giving rewards and punishments can increase students' interest in participating in Catholic religious studies at school. This can be seen from the enthusiasm with which students participate in Catholic Religious Education lessons. So that Catholic religious education lessons are expected to be increasingly in demand in the future.